Theorizing and analyzing language teacher agency - Kayi-Aydar, Hayriye; Gao, Xuesong; Miller, Elizabeth R., 1965-; Varghese, Manka, 1969-; Vitanova, Gergana (Bristol ; Blue Ridge Summit : Multilingual Matters, 2019)
"This volume examines the agency of second/foreign language teachers in diverse geographical contexts. It offers new understandings and conceptualizations through a variety of types of empirical data, as well as demonstrating the use of different methodologies to analyze the multidimensional, dynamic and complex nature of language teacher agency"--
Language teacher agency : major theoretical considerations, conceptualizations, and methodological choices / Hayriye Kayi-Aydar -- Examining high school English language learner teacher agency : opportunities and constraints / Aliza Fones -- "What if you don't have boots," let alone bootstraps? an ELL teacher's use of narrative to achieve and generate agency in the face of contextual constraints / G. Sue Kasun, J. Spencer Clark, A. Jyoti Kaneria and Emmie Staker -- Language teacher agency and high-stakes teacher evaluation : a positioning analysis / Amber N. Warren -- Using actor-network theory to problematize agency and identity formation of Filipino teachers in Japan / Alison Stewart -- World language teachers performing and positioning agency in classroom target language use / Michele Back -- Bi/multilingual teachers' professional holistic lives : agency to enact inquiry-based and equity-oriented identities across school contexts / Patricia Venegas-Weber -- English language teachers' agency and identity mediation through action research : a Vygotskian sociocultural analysis / Emily Edwards -- Problematizing English language teaching in China through a local Chinese English teacher agency lens / Wenjing Li and Peter De Costa -- Teacher authority and the collaborative construction of agency in second language writing instruction / Patricia Mayes -- Language teacher agency : a critical realist perspective / Karin Zotzmann -- Volunteer teacher agency in a church-based ESL program : an ethnography / Xia Chao -- English language instructors, medium of education, and professional agency : an Indian perspective / Priti Sandhu.
Includes bibliographical references and index.
Keywords: English teachers -- Training of -- Social aspects; English teachers -- Training of -- Research -- Methodology